MODEL KONSEPTUAL PENGELOLAAN PENGETAHUAN DI POKDARWIS WONDERFUL SANGIRAN DENGAN PENDEKATAN SOFT SYSTEM METHODOLOGY - Latuperissa, Rudy (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2020)
This study aims to develop a conceptual model of knowledge management for Kelompok Sadar Wisata (a tourism-aware group) Pokdarwis Wonderful Sangiran. Knowledge management system is needed to develop their skill, ability and maintain their adequate knowledge and information as a knowledge-based tourism guide. Conceptual Model is developed using the Soft System Methodology approach, consisting of 7 stages, starting from the situation considered as problematical, the Rich-picture development, the root definition, the conceptual model development, the comparison conceptual model with reality, and determining a change and proposal. The preparation of rich-picture is based on the primary data obtained from several informants, i.e member of Pokdarwis, researchers, academics and government officials selected using purposive sampling. This employs a qualitative method to develop a conceptual model that could bring out ideas for Pokdarwis activities in the future in relation to their knowledge management. Recommendations on developing a knowledge management system could be the media for knowledge transfer and knowledge sharing within the Pokdarwis itself, from Pokdarwis member to researchers, academics, government to Pokdarwis member, and from Pokdarwis to the younger generation. Knowledge management conception in the form of personalization and codification and knowledge creation could be referred to in developing the technology-based knowledge management system.Keyword: soft system methodology; conceptual model; knowledge creation; knowledge management system ABSTRAKPenelitian ini bertujuan untuk membangun sebuah Model Konseptual pengelolaan pengetahuan bagi Kelompok Sadar Wisata (Pokdarwis) Wonderful Sangiran. Sistem pengelolaan pengetahuan dibutuhkan untuk mengembangkan kemampuan dan keterampilan anggota Pokdarwis serta menjaga kecukupan informasi dan pengetahuan sebagai pemandu wisata berbasis pengetahuan. Model Konseptual dibangun menggunakan pendekatan Soft System Methodology (SSM). Pendekatan ini terdiri dari 7 tahapan, mulai dari tahap pengenalan masalah, tahap pengembangan Rich-picture, tahap pendefinisian akar masalah, tahap pengembangan model konseptual, tahap pembandingan model konseptual dengan realitas, tahap menetapkan perubahan hingga tahap menentukan usulan. Pengembangan Rich_picture didasarkan pada data primer yang diperoleh dari beberapa informan, antara lain: anggota Pokdarwis, peneliti, akademisi dan pegawai pemerintah, yang dipilih berdasarkan kriteria tertentu (purposive sampling). Penelitian kualitatif yang dilakukan menghasilkan sebuah model konseptual sebagai usulan bagi aktivitas atau kegiatan Pokdarwis di masa mendatang, terkait dengan pengelolaan pengetahuan. Rekomendasi pengembangan sistem pengelolaan pengetahuan dapat menjadi media Knowledge Transfer dan knowledge sharing, baik bagi inter-anggota Pokdarwis, maupun dari peneliti, akademisi, pemerintah ke anggota Pokdarwis, serta dari anggota Pokdarwis ke generasi muda. Konsepsi pengelolaan pengetahuan berupa strategi personalisasi dan kodifikasi serta proses knowledge creation/conversion dapat menjadi acuan dalam pengembangan sistem pengelolaan pengetahuan berbasis Teknologi Informasi.